Parallel - Lehmann, Matthias (Oni Press, 2023)
Karl Kling's story is one of revelations, and these he has addressed in a letter to his daughter, Hella, who had disowned Karl many years ago. Karl's letter is a cri de coeur from a father to a daughter he never really got to know, and he comes clean to her about his failed marriages, his fractured family relations--and his love for men.